Intramolecular O‐arylation using nano‐magnetite supported N‐heterocyclic carbene‐copper complex with wingtip ferrocene. (9th July 2019) - Naikwade, Altafhusen; Jagadale, Megha; Kale, Dolly; Gajare, Shivanand; Bansode, Prakash; Rashinkar, Gajanan
Abstract : Nano‐magnetite supported N ‐heterocyclic carbene‐copper complex with wingtip ferrocene has been prepared via multi‐step procedure. The complex has been characterized by various analytical techniques such as fourier transform infrared (FT‐IR), fourier transform Raman (FT‐Raman), X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), transmission electron microscopy (TEM) and vibrating sample magnetometer (VSM) analysis. The catalytic activity of the complex has been exploited in intramolecular O‐arylation of o ‐iodoanilides under heterogeneous conditions. The complex could be successfully recycled up to twelve consecutive cycles. Abstract : Nano‐magnetite supported N ‐heterocyclic carbene‐copper complex with wingtip ferrocene was synthesized. The complex was employed efficiently for intramolecular O‐arylation of o ‐iodoanilides. The complex could be successfully reused up to twelve consecutive runs.